EARLY DIAGNOSIS AND TREATMENT OF THE POSTERIOR URETHRAL VALVE - Холметов Ш. Ш.; Хотамов Х. Н. (Web of Journals Publishing, 2025)
Posterior urethral valves are the leading cause of urinary tract obstruction in children, associated with the risk of renal failure and bladder dysfunction. A review of the literature, including peer-reviewed sources and meta-analyses, discusses the early diagnosis and treatment of this pathology.
Keywords: Posterior urethral valve, urinary tract obstruction, early diagnosis.